Pengaruh Rasio Massa Air dan Udara Terhadap Unjuk Kerja Forced Draft Wet Cooling Sudut Inklinasi Splash Fill Berlubang - Khairul Umurani; Ahmad Syuhada; M.I.. Maulana; Zahrul Fuadi (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
This study aims to experimentally analyse the performance of a forced wet cooling tower (WTC) using multilevel inclined perforated splash fill. The hot water temperature is set at 60 C; Packing has an inclination angle of 15o, 20o, 25o and a perforation ratio of 2.6%, which consists of five levels of galvanised plate fill. The water flow rate is ± 0.0917 kg/s, and the five variations of air flow rate are 0.02033, 0.02631, 0.02995, 0.03770, and 0.04261 kg/s. The inlet hot water temperature is 60 C. In this study, it can be seen that the ratio of water mass and air mass affects the performance of the cooling tower